Micronutrient Intake and Risk of Hematological Malignancies in Adults: A Systematic Review and Meta-analysis of Cohort Studies. (18th August 2018) - Psaltopoulou, Theodora; Ntanasis-Stathopoulos, Ioannis; Tsilimigras, Diamantis I.; Tzanninis, Ioannis-Georgios; Gavriatopoulou, Maria; Sergentanis, Theodoros N.
Abstract: There has been accumulating evidence that several micronutrients may play a protective role in the risk of solid cancers. However, their role in hematological malignancies remains to be elucidated; this meta-analysis aims to evaluate the associations between micronutrient intake as well as supplementation and risk of hematological cancer in adults. Eligible cohort studies (examining intake of vitamin A, vitamin C, vitamin D, vitamin E, lycopene, folate, iron, carotenoids, beta-carotene, selenium, pyridoxine) were sought in PubMed up to July 31, 2016. Random-effects models were used for the calculation of pooled relative risks (RR) with their 95% confidence intervals (CI). Twelve cohort studies were deemed eligible. Null associations were noted regarding supplemented vitamin A (pooled relative risk [RR] = 0.92, 95% confidence interval [CI]: 0.80–1.07), supplemented vitamin C (pooled RR = 1.00, 95%CI: 0.90–1.12), total vitamin D (pooled RR = 1.05, 95%CI: 0.91–1.20), supplemented vitamin E (pooled RR = 0.98, 95%CI: 0.88–1.10), and dietary lycopene intake (pooled RR = 1.00, 95%CI: 0.86–1.16) and the risk of non-Hodgkin lymphoma. No summary estimates are provided for other hematological malignancies due to the limited number of studies. Future prospective trials should be conducted for a better understanding of this field; especially regarding Hodgkin lymphoma, leukemia and plasma cell neoplasms, on which data are scarce.